A Straightforward Synthesis of N-Substituted Ureas from Primary Amides - Saraiva Rosa, Nathalie; Glachet, Thomas; Ibert, Quentin; Lohier, Jean-François; Franck, Xavier; Reboul, Vincent (Synthesis, 2020)
A direct and convenient method for the preparation of N-substituted ureas is achieved by treating primary amides with phenyliodine diacetate (PIDA) in the presence of an ammonia source (NH3 or ammonium carbamate) in MeOH. The use of 2,2,2-trifluoroethanol (TFE) as the solvent increases the electrophilicity of the hypervalent iodine species and allows the synthesis of electron-poor carboxamides. This transformation involves a nucleophilic addition of ammonia on the isocyanate intermediate generated in situ by a Hofmann rearrangement of the starting amide.
Keywords: amides; ureas; hypervalent iodine; Hofmann rearrangement; isocyanates